Evaluación de Distintos Métodos de Secado de Grano en Quinua (chenopodium quinoa willd.). Mediante el Uso de Horno Convencional y Microondas a diferentes temperaturas y potencias, en el Campus Salache. 2017-2018. - Espinoza Toscano, Javier Alexander (2018)
The present investigation was carried out in the Province of Cotopaxi, Canton Latacunga, Eloy Alfaro parish, Salache sector in the CEASA (Salache Academic and Experimental Center). The main objective was to evaluate the drying of the quinoa grain (Chenopodium quinoa Willd.). At different temperatures using a Conventional Oven and a Microwave Oven with a Temperature Control. The purpose of these methods was to reduce the percentage of humidity in the grain, shortening the drying time, compared to traditional drying, which requires a long period of time, which it is prone to external contaminants. The drying was carried out in a microwave oven with temperature controller and conventional oven until it reached 10% humidity. The drying curves for each treatment were obtained, later germination tests were carried out to check the viability of the quinoa seed. The best viability results were obtained in the Microwave Oven with Temperature Control at 45 and 55 ° C, whose data of germination are similar to those observed after Natural Drying, however between these two treatments the most appropriate according to the present investigation is the Microwave Oven at 55 ° C, since it reduces in 50 minutes the required times to 45 °C. Consequently, it is recommended to use the microwave oven drying method with a temperature controller at 55 °C, taking into account the different temperature variations.